Transforming vision into action: exploring collaborative governance strategies in the development of the Nusantara New Capital City - Rusmiyati, Rusmiyati; Rahmadany, Andi Fitri (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
The research purpose to examine collaborative governance, the potential and opportunities for the Nusantara New Capital City. The research design utilizes a qualitative exploratory method, where collected data is then analyzed using descriptive techniques. The results showed that the realization of collaborative governance in the development of Nusantara New Capital City has not been optimized due to less intensive and sustainable communication.; low levels of trust among local stakeholders; failure to build ownership and lack of transparency in achievements; lack of shared vision, mission, and perspective on resolving common issues; suboptimal realization of common values in the development of Nusantara New Capital City; achievement of only 38.1% completion progress in development; and the realization of strategic planning being less accelerated. The model for the collaborative governance optimization of Nusantara New Capital City is developed as a model emphasizing the empowerment of equality and proportional aspects of local stakeholders supported by accommodated regulation. The model can be applied to various collaborative governance objects and in other regions because it is developed according to the flexibility, conditionality, actuality, and factual nature of the issues